Generation of frequency-tunable pulsed terahertz radiation by a Cr : forsterite laser system with an acoustooptical control of the pulse temporal profile. (December 2016) - Ovchinnikov, A.V.; Chefonov, O.V.; Molchanov, V.Ya.; Yushkov, K.B.; Vicario, C.; Hauri, C.
Abstract: We report the experimental results on generating pulsed terahertz (THz) radiation, frequency-tunable within the range . The THz pulse generation was implemented using the method of optical rectification of femtosecond laser pulses in the nonlinear organic crystal OH1. The frequency tuning of the THz radiation was provided by adaptive phase – amplitude modulation of the pump pulses from the Cr : forsterite laser system with a radiation wavelength of using the acoustooptical dispersion delay line.